Development and validation of the coach's task presentation scale: A quantitative self-report instrument - Tristán Rodríguez, José Leandro; López Walle, Jeanette M.; Tomás, Inés; Cantú Berrueto, Abril; Pérez García, José Alberto; Castillo Fernández, Isabel María (Elsevier Science, 2016)
Objective: A major concern for coaches is the transmission of effective information in the moments before sport practice, when they communicate to players what they are supposed to do and how (Rink, 1994). The present study's main objective was to cover a gap in the sport psychology measurement field and to develop and validate a quantitative self-report instrument to measure the effectiveness of coaches' task presentation for athletes. The resulting instrument was the Escala de Presentacion de las Tareas por Parte del Entrenador (EPTE) [Coach's Task Presentation Scale]. Design: The two studies developed to validate the EPTE used a cross-sectional research design. Method: Participants in Study 1 included 830 college athletes aged between 18 and 27, who completed the EPTE. Participants in Study 2 included 677 college athletes aged between 17 and 29, who completed the EPTE and other questionnaires measuring coach's interpersonal style (autonomy support and controlling style) and basic psychological needs satisfaction/thwarting. Study 1 comprised translation, item formulation and examination of the reliability and factorial structure of the EPTE. Study 2 provided evidence of factorial validity and evidence of validity based on relationships with other variables in the context of the Self Determination Theory (Deci & Ryan, 2000). Results: The results of reliability analysis and the different sources of validity provided, demonstrated the instrument's adequacy in terms of psychometric properties. Conclusions: The EPTE is a valid, reliable scale that can be used to measure the effectiveness of task presentation by coaches, according to the perception of athletes.